Compaction processes and rock properties in uplifted clay dominated units– the Egersund Basin, Norwegian North Sea. (December 2015) - Kalani, Mohsen; Jahren, Jens; Mondol, Nazmul Haque; Faleide, Jan Inge
Abstract: A thick succession of fine-grained sediments in any sedimentary basin can serve as source (if organic-rich) and top seals. Both sealing and petroleum generation capacity of any fine-grained succession is dependent on compaction history (mechanical and chemical compactions) of the sediments. In the Egersund Basin, a thick succession of fine-grained sediments of Upper Jurassic-Lower Cretaceous age overly Middle Jurassic reservoir sands. The Egersund Basin, however, has experienced a complex depositional and tectonic history, particularly, late exhumation (Neogene) which complicates the overall burial, thermal and pressure history. In this study, petrophysical and acoustic properties (bulk density and P-wave velocity) of 10 exploration wells from two neighboring blocks in the Egersund Basin were utilized to investigate compaction processes in the area. In addition, X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses from selected wells and available total organic carbon (TOC) data were used as guide to interpret the compaction processes and resulting rock properties. The results show that the transition from mechanical to chemical compaction is not sharp. The onset of chemical compaction imposes a measurable deviation in the burial depth trends of the petrophysical properties expected from purely mechanical compaction. The continuation of the depth related trends however, indicates that chemical compaction may occur in concurrent with continuing mechanical compaction. The observed compaction varies between the different clay dominated stratigraphic units; indicating that the major control on both mechanical and chemical compaction is the primary sediment composition. Highlights: Physical properties of mudrocks were compared with those of synthetic mudstones. Indications of the onset of chemical compaction were inferred from well log data. Petrographic and mineralogical evidences of chemical compaction were presented. Compaction implications for exhumation estimation were discussed.